Assessment of heart-evoked potentials in hypertensive patients - A. A. Sukmanova; I. A. Minenko; A. S. Limonova; K. A. Guseynova; Z. B. Bashankaeva; V. V. Moiseeva; A. I. Ershova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
In recent years, interoception, described as the ability to perceive signals from internal organs, has been actively studied. However, the relationship between cardiovascular diseases and neurophysiological characteristics of interoception remains poorly understood.Aim. In this work, we studied neurophysiological markers of interoception in a group of patients with hypertension. Heart-evoked potentials (HEPs) were used as neurophysiological markers.Material and methods. The study included 41 patients with HTN (2250 years old, 80,5% received antihypertensive therapy) and 41 people from the control group (26-50 years old), matched for sex and age. Interoception was studied at the behavioral level by heartbeat tracking task (HTT) and at the neuronal level by the electroencephalography method to record HEPs. Participants filled out the Toronto Alexithymia Scale questionnaire.Results. No significant differences in the accuracy of heartbeat sensations and HEP amplitudes were found between the HTN and control group, as well as significant relationships between accuracy of heartbeat sensations and HEP amplitudes in both groups. Significant positive correlations were found between the HEP amplitudes and the alexithymia indices in both groups.Conclusion. No differences in HEP amplitudes were found between the patients with hypertension and the control group. However, for the first time, a relationship was demonstrated between difficulties in recognizing emotions and HEP amplitudes in hypertensive patients, confirming the hypothesis about the interaction of these processes at insular cortex level.